The Role of Bilingual Workers without Professional Mental Health Training in Mental Health Services for Refugees - Egli, Eric.; Minnesota Univ., Minneapolis. Refugees Assistance Program - Mental Health Technical Assistance Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This paper discusses the use of bilingual workers who do not have formal mental health training as mediators and providers of mental health care for refugees. The introduction provides a background discussion of the need for refugee mental health services, the characteristics of bilingual mental health workers, and the work places and expectations of the bilingual worker. After a brief discussion of the problem of job title, the functions of bilingual workers are enumerated and described: translation, interpretation, culture broker, outreach and community education, and mental health counselor or cotherapist. The next section addresses special issues and problems arising with bilingual workers, beginning with the psychosocial and interpersonal dynamics of the bilingual worker's role as interpreter between patient and clinician. Other issues include training, certification and quality assurance, bilingual career development, burnout among bilingual workers, and the potential for the abuse of power by bilingual workers. The discussion concludes with considerations for the recruiting and hiring of bilinguals. References are included. (TE)
Availability: Refugee Assistance Program--Mental Health Technical Assistance Center, University of Minnesota, Box 85, Mayo, Minneapolis, MN 55455.
Sponsoring Agency: National Inst. of Mental Health (DHHS), Rockville, MD.
Contract Number: NIMH-278-85-0024-CH.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingualism; Counselor Certification; Counselor Evaluation; Counselor Training; Cross Cultural Training; Employer Employee Relationship; Intercultural Communication; Interpreters; Mental Health Programs; Paraprofessional Personnel; Psychiatric Aides; Recruitment; Refugees; Semiskilled Workers; Translation; Refugee Mental Health; Refugee Assistance; Information Analyses; Reports, Research